Implementation of Differentiated Learning Model in Independent Curriculum in PAI Subject For Grade Xi (F1) at SMAN 13 Padang - Surya Afdal; Ismail Syakban; Kisnovita Kisnovita; Muchlis Muchlis (Jurnal Kajian dan Pengembangan Umat, 2025)
This study aims to describe the implementation of differentiated learning within the Merdeka Curriculum in Islamic Religious Education (PAI) for Grade XI students at SMAN 13 Padang. A qualitative approach with a phenomenological method was employed, with the researcher acting as the main instrument assisted by interview guides, observation sheets, and documentation formats. Data were collected through interviews with teachers, students, and the vice principal, classroom observations, and documentation of teaching materials and student evaluations. The data were analyzed through data reduction, display, and conclusion drawing, while data credibility was ensured using source and technique triangulation. The findings reveal that differentiated learning implementation was carried out in three stages. First, in the planning stage, teachers conducted diagnostic assessments to map students’ readiness, interests, and learning profiles as the basis for developing learning modules and adaptive strategies. Second, in the implementation stage, teachers adjusted the content, process, and product of learning to suit students’ characteristics through creative techniques such as appreciation, ice breaking, MARSHA, crossword puzzles, and group discussions. Third, in the evaluation stage, authentic formative and summative assessments were applied, including oral and written tests as well as attitude assessments. The results emphasize contextual understanding, active student engagement, and the internalization of religious values. This study provides empirical evidence that differentiated learning can be effectively implemented in PAI, offering both theoretical implications for instructional design and practical recommendations for teachers in applying the Merdeka Curriculum.Keywords: Differentiated Larning; Merdeka curriculum; Islamic Religious Education